Odpowiedzi

2010-03-10T17:25:08+01:00
A)6(x-4)-2= 6x-24-2= 6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3 = -x+5
c)-3(y-2)+4(y+2)= -3y+6+4y+8= y+14
d)5(x-y-1)-4(x+2)= 5x-5y-5-4x-8= x-5y-13
e)2(3a+b)-2(a-b)= 6a+2b-2a+2b= 4a+4b
f)1/2(4x-4)-2x= 2x-2-2x= -2
g)x(x-1)-3(x²-x)= x²-x-3x²+3x= -2x²+2x
h)5a(a-3)?3a(a-5)= 5a²-15a+3a²-15a= 8a²-30a lub 5a²-15a-3a²+15a= 2a²
i)3x(x+1/3y)-2y(1/2x-1/2)= 3x²+3xy-xy+y= 3x²+2xy+y
2010-03-10T17:27:33+01:00
A)6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)1/2(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x
h)5a(a-3)3a(a-5)=5a²-15a+3a²-15a=8a²-30a
i)3x(x+1/3y)-2y(1/2x-1/2)=3x²+3xy-xy+y= 3x²+2xy+y

pozdrawiam ;**